Dosimetric Evaluation of Dose Calculation Uncertainties for MR-Only Approaches in Prostate MR-Guided Radiotherapy - Coric, Ivan; Shreshtha, Kumar; Roque, Thais; Paragios, Nikos; Gani, Cihan; Zips, Daniel; Thorwarth, Daniela; Nachbar, Marcel (Frontiers in Physics, 2022)
Purpose: Magnetic resonance imaging guided radiotherapy (MRgRT) allows treatment plan adaptation on the MRI of the day. For dose calculations, a structure-specific bulk relative electron density (RED) overwrite derived from a planning computed tomography (CT) poses as one possible treatment workflow. However, this approach introduces uncertainties due to assignment of mean densities and requires a planning CT. The aim of this study was to investigate the uncertainty of the used patient-specific (PSCT) dose calculation in contrast to the correct calculation on a CT and compare to MR-only workflows using population-based bulk ED (PBCT) and artificial intelligence–based pseudo-CTs (AICT). Methods: Twenty primary prostate cancer patients treated on the 1.5 T MR-Linac were chosen from the clinical database, based on best visual congruence between the planning CT and daily MRI. CT-based reference dose distribution was compared to different pseudo-CT approaches. 1) For PSCT, mean REDs for the femur, pelvis, sacrum, rectum, bladder, and patient were assigned based on individual mean CT densities. 2) Population-based mean REDs were derived based on 50 previous, independent patients and assigned to the structures for the PBCT approach. 3) An AI model for pseudo-CT generation was trained using end-to-end ensembled self-supervised GANs and used to create AICTs from T2w-MRIs. For comparison, the CT was registered to the MRI, structures rigidly propagated, and treatment plans recalculated. Differences of DVH parameters were analyzed, and dose distributions were compared using gamma analysis. Results: All approaches were able to reproduce the dose distribution accurately, according to a gamma criterion of 3%/3 mm, with pass rates greater than 98%. Applying a 2%/2 mm criterion, the median gamma pass rates for PSCT, PBCT, and AICT resulted in 98.6%, 98.2%, and 99.0%, respectively. The median differences for PTV D98% resulted in 0.13 Gy for AICT, −0.31 Gy for PBCT, and −0.32 Gy for PSCT. The OAR-related DVH parameter showed similar results between the three investigated methods. Conclusion: In this study, a detailed analysis of uncertainties of MR-only treatment planning concepts for pelvic MRgRT was performed. Both a PBCT and an AICT approach, which bypass the need for a planning CT, may be considered clinically acceptable while reducing imaging dose and registration issues.